Impact of emissions and +2 °C climate change upon future ozone and nitrogen dioxide over Europe. (October 2016) - Watson, Laura; Lacressonnière, Gwendoline; Gauss, Michael; Engardt, Magnuz; Andersson, Camilla; Josse, Béatrice; Marécal, Virginie; Nyiri, Agnes; Sobolowski, Stefan; Siour, Guillaume; Szopa, Sophie; Vautard, Robert
Abstract: The evolution of ozone and nitrogen dioxide over Europe between the present day and a future period with a +2 °C global warming relative to the pre-industrial climate was studied using four offline chemistry transport models, each driven by a different climate model. Given the recent outcome of the COP21 negotiations, understanding the implications of climate change around the +2 °C threshold has never been more pressing or relevant. One of the objectives of this study was to show how changes in anthropogenic emissions and +2 °C climate change are expected to affect future air quality, which may have important implications upon human health. It was found that a +2 °C climate change alone was responsible for a modest, and not statistically significant, increase in surface O3 concentrations (of between −0.1–0.8 ppb in the summer averaged over the European domain) compared to the present climate. Two different emission scenarios were used for the future time period in order to provide an estimate of the extent of air pollution reductions that could occur if (a) all currently planned air quality legislation is implemented and (b) all maximum technologically feasible emission reductions are implemented. The results showed that summer O3 could be reduced by between 4 and 5 ppb under a current legislation scenario, with at least 3 ppb of further reductions under the maximum mitigated scenario. Calculations of summer ozone enhancement were used as a metric to analyse the results after having removed background ozone level changes. In conclusion it was found that future air quality on a regional scale will depend upon the implementation of effective emission reduction policy; the positive effects of which should not be hindered by a +2 °C global warming. Highlights: The impacts of a +2 °C climate change upon future O3 and NO2 were studied. Long (30-year) simulations were performed with a set of 4 chemical transport models. Unique approach: future time period centred on +2 °C warming, rather than fixed years. Reductions of anthropogenic emissions significantly improved future air quality. Isolated impacts of climate change upon O3 were not statistically significant.